3D Z-scheme conjugated polymer/Cu2O for organic photoelectrochemical transistor bioassay - Wang, Cheng-Shuang; Chen, Jia-Hao; Zhang, Pan-Ke; Yuan, Cheng; Yu, Si-Yuan; Zhao, Wei-Wei; Xu, Jing-Juan (Biosensors & bioelectronics, 2025)
Organic photoelectrochemical transistor (OPECT) is an emerging technology studying photo-electric-biological recognition events. Here, this work reports the three-dimensional (3D) Z-scheme poly (1,4-diethynylbenzene) (pDEB)@Cu2O heterojunction as a high-efficacy photogating module and its application for OPECT bioassay. Specifically, 3D Z-scheme pDEB@Cu2O heterojunction enabled fast charge transport and ion diffusion in the system, achieving remarkable amplification capability with a current gain as high as ca. 9.6 × 103. By linking with GOx-labeled sandwich immunorecognition, the impact of GOx-generated H2O2 on the OPECT made possible the sensitive bioassay. Exemplified by carcinoembryonic antigen (CEA) as the model target, the OPECT device achieved a linear detection range spanning from 100 fg/mL to 100 ng/mL and coupled with a detection limit as low as 72 fg/mL. This work provided a generic and extensible platform for the designation of novel bioassay systems. [Display omitted]